AN HIGHER WHITE-COAT EFFECT IN THE FIRST HOURS OF AMBULATORY BLOOD PRESSURE MONITORING IS ASSOCIATED WITH MORE BLOOD PRESSURE PEAKS DURING THE WHOLE DIURNAL PERIOD. (June 2018) - Salvo, F.; Berardi, M.; Errani, A.R.; Muzzulini, C.L.; Morganti, A.
Abstract : Objective: White-coat effect (WCE) is a common finding also in ambulatory blood pressure monitoring (ABPM) and like in office blood pressure (BP) measurement can determine an over-diagnosis of arterial hypertension. In our previous work we found that WCE magnitude (WCEm) is correlated with an higher BP variability during the entire 24-hours ABPM period but the effective BP load remain to be established. Design and method: We analysed 421 ABPMs (M/F 146/275) characterized by the first systolic BP value at least 10 mmHg higher than mean diurnal systolic BP (mDSBP). WCEm was evaluated as the mean value of the first two hours of recording, both for systolic and diastolic BP (sysWCEm and diaWCEm, respectively). The diurnal BP load was estimated with BP peaks, i.e. the number of systolic and diastolic BP values respectively 10 and 5 mmHg higher than mDSBP and mean diurnal diastolic BP (mDDBP). We evaluated the correlations between WCEm, BP peaks and drug classes (angiotensin-converting enzyme/angiotensin receptor blockers, beta-blockers, calcium channel blockers, thiazide diuretics, alpha-blockers, central alpha-agonists and anti-aldosterone) with a multivariate regression analysis with a p-value < 0.01 considered as statistically significant. Results: Mean age was 65 ± 1 years (M/F 66 ± 1/64 ± 1 years, n.s.) and overall mDSBP and mDDBP were 137 ± 1 and 79 ± 0.5 mmHg, whereas sysWCEm and diaWCEm were respectively 150 ± 1 and 86 ± 1 mmHg, without gender differences. Systolic and diastolic peaks were respectively 12.5 ± 0.1 and 13.5 ± 0.1; only the first was directly correlated with age (r = 0.21; p < 0.01) whereas neither of the two was correlated with drug therapy. Both systolic and diastolic peaks were significantly correlated with sysWCEm (respectively r = 0.17 and r = 0.19; p < 0.01) but not with diaWCEm; they were also correlated with mDSBP and mDDBP (respectively r = 0.35 and r = 0.31; p < 0.01). Conclusions: In patients with an higher sysWCEm, systolic and diastolic BP peaks are increased confirming an influence of WCE on the entire diurnal period of ABPM, suggesting that in patients with WCE the alarm reaction persists well beyond the two initial hours of recording alarm.